Highly permeable novel PDMS coated asymmetric polyethersulfone membranes loaded with SAPO-34 zeolite for carbon dioxide separation - Haider, Bilal; Dilshad, Muhammad Rizwan; Ur Rehman, Muhammad Atiq; Vargas Schmitz, Jürgen; Kaspereit, Malte (Separation and Purification Technology, 2020)
Novel asymmetric polyethersulfone membranes loaded with SAPO-34 particles were prepared using phase inversion technique and then surface coated with PDMS using spin coating method. The mixed matrix membranes were then characterized by FTIR, TGA, SEM-EDX and gas permeation analysis. Effect of SAPO-34 loading alongwith operating pressure was also analyzed on gas permeation properties of both coated and uncoated membranes. SAPO-34 loading resulted in improvement of permeability of all the gases without much decrease in CO2 ideal selectivity with respect to methane and nitrogen whereas PDMS coating resulted in improvement of ideal selectivity of CO2 at the expense of decrease of permeance of all the gases. It was found that PDMS coated PES membrane, loaded with 30 wt.% SAPO-34, having thickness of 45 µm, demonstrated high CO2 permeance of 641.77 GPU, CO2/CH4 ideal selectivity of 4.45 and CO2/N2 ideal selectivity of 12.45, respectively at 20 bar and 25 °C. It was found that the performance of this membrane crossed the Robeson upper bound limit 2008 for CO2/N2 separation whereas for CO2/CH4 separation it crossed the previous upper bound limit 1991. Finally, the performance of this membrane was also analyzed under mixed gas conditions for CO2/CH4 separation at high pressure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Asymmetric; Gas separation membranes; PDMS coating; Polyethersulfone; SAPO-34

Model development for the separation of a strongly adsorbing gas mixture on a semi-pilot scale adsorber - Vargas Schmitz, Jürgen; Kriesten, Martin; Hartmann, Martin; Kaspereit, Malte (Separation and Purification Technology, 2019)
A detailed model is developed for the separation of strongly adsorbing gas mixtures at semi-pilot scale. It assumes a non-isothermal compressible transport-diffusion mechanism in the adsorber and dispersed compressible flow in the periphery, respectively. A methodology is proposed for efficient system analysis and parameter determination, leading to high model accuracy. The separation of N-2 and CO2 on the carbon molecular sieve CMS-H2 55/2 serves as example problem. Based on experimental equilibrium data for different temperatures, the applicability of different adsorption isotherm models is investigated for the single components. Isosteric heats of adsorption and their dependency on adsorbate loadings are determined by an analysis using the virial isotherm. A single reference experiment - an adsorption-desorption breakthrough for a diluted gas mixture - allows estimating heat and mass transfer coefficients and investigating the role of competitive adsorption and heat effects. The final model accurately predicts compositions, temperatures, and flow rates for a complete set of adsorption and desorption experiments in a broad range of conditions.
CRIS-Team WoS Importer:2019-05-03

On the dynamics of gas adsorption processes for systems governed by different phenomena - Hartmann, Martin; Vargas Schmitz, Jürgen; Hovestadt, Maximilian; Kriesten, Martin; Hartmann, Michael; Kaspereit, Malte (22nd International Congress of Chemical and Process Engineering, CHISA 2016 and 19th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction, PRES 2016, 2016)

Scale-up of the Synthesis of Zeolitic Imidazolate Framework ZIF-4 - Hovestadt, Maximilian; Vargas Schmitz, Jürgen; Weissenberger, Tobias; Reif, Florian; Kaspereit, Malte; Schwieger, Wilhelm; Hartmann, Martin (Chemie Ingenieur Technik, 2017)
A new synthesis route for the zeolitic imidazolate framework ZIF-4 is reported. About 200 g of ZIF-4 are prepared by sonothermal synthesis from ZnO at room temperature. The ZIF-4 prepared by sonothermal synthesis is comparable to the ZIF-4 synthesized by the pathway reported in literature with respect to the powder X-ray diffraction pattern, particle size, and separation potential for olefin-paraffin gas mixtures. Moreover, the separation potential of ZIF-4 is compared to commercial adsorbents like carbon molecular sieves and zeolites.
Keywords: Adsorption; Ethylen; Porosity; Ultrasound-assisted synthesis

Shaping of Flexible Metal-Organic Frameworks: Combining Macroscopic Stability and Framework Flexibility - Kriesten, Martin; Vargas Schmitz, Jürgen; Siegel, Jonas; Smith, Christopher E.; Kaspereit, Malte; Hartmann, Martin (European Journal of Inorganic Chemistry, 2019)
A facile extrusion approach that can fully retain the breathing behavior of flexible metal-organic frameworks (MOF) like MIL-53 and MIL-53-NH2 employing methyl cellulose as binder is reported. Shaped MOF extrudates were extensively characterized by nitrogen sorption, X-ray diffraction, thermogravimetric analysis and scanning electron microscopy. A detailed study on the mechanical stability of MIL-53 extrudates with different amounts of binder reveals an increase in stability at low binder fractions while the maximum in attainable stability is reached at 5 wt.-% binder. In-situ XRD studies in CO2 atmosphere and under humid conditions, respectively, demonstrate the reversibility in breathing behavior of the MIL-53 extrudates without affecting the phase transition kinetics. High-pressure methane and carbon dioxide isotherms on MIL-53 and MIL-53-NH2 extrudates exhibit loadings that are comparable to the uptake of the pristine powder. The shaping approach reported herein paves the way for using flexible MOF structures in technical applications.
CRIS-Team WoS Importer:2019-11-15

Systematische Entwicklung adsorptiver Gastrennprozesse für Mehrstoffgemische - Vargas Schmitz, Jürgen (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
Eine Methodik zur Entwicklung eines detaillierten Anlagenmodells für die Trennung stark-adsorbierender Gasgemische wird präsentiert. Das Modell besteht aus einem kompressiblen, nichtisothermen Transport-Dispersions-Modell für den Adsorber und einem axial-dispersen, kompressiblen Modell für die peripheren Volumina. Die Methodik beschreibt die systematische Auswahl der Bedingungen von Adsorptionsgleichgewichtsmessungen, die zur korrekten Parametrisierung von Adsorptionsisothermenmodellen erforderlich ist. Dabei werden die Oberflächenheterogenität sowie die Abhängigkeit der isosteren Adsorptionswärme von Beladung und Temperatur mit dem Virial-Ansatz im Detail untersucht. Gleichermaßen werden zur Parametrisierung der Wärme- und Stoffübertragung Richtlinien zur Auslegung dynamischer Versuche in Form von Adsorptions-Desorptionszyklen mit möglichst hohem Informationsgehalt. In diesem Zusammenhang wird ein Kompetitivitätsgrad eingeführt, anhand dessen die Ausprägung nichtlinearer dynamischer Effekte in binären und pseudobinären Systemen untersucht werden kann. Eine erweiterte Korrelation des Wärmeübertragungskoeffizienten zwischen dem Adsorberbett und der Adsorberwand, die die lokalen Änderungen der Wärmeleitfähigkeit in der fluiden Phase mit einem pseudostatischen Beitrag berücksichtigt, wird vorgeschlagen. Die Methodik wird auf das Modellsystem H2/N2/CH4/CO2 auf einem Kohlenstoffmolekularsieb angewendet. Das entwickelte Modell kann mit hoher Genauigkeit Temperatur-, Zusammensetzungs- und Volumenstromverläufe binärer und pseudobinärer Adsorptions-Desorptionszyklen in einem breiten Bereich an Temperaturen, Zusammensetzungen, Drücken und Volumenströmen vorhersagen. Weiterhin kann das Modell ternäre und Einkomponentensysteme beschreiben. Durch Simulationsstudien wird die Relevanz der Kompetitivität, Adsorptionskinetik, Wärmeübertragung und Totvolumina evaluiert.<br
Keywords: gas adsorption processes; pressure-swing adsorption; heat of adsorption; breakthrough curve; modelling; simulation; Tóth adsorption isotherm; virial adsorption isotherm; competitive adsorption; heat transfer; carbon molecular sieve; heterogeneous surface; compressible non-isothermal transport-dispersion model; model parametrization; bulk separation